IMPLEMENTATION OF WORDWALL TO IMPROVE STUDENTS' CRITICAL THINKING SKILLS AT SMPN 8 BANJARMASIN - Handy, Muhammad Rezky Noor; Emelia, Emelia; Subiyakto, Bambang; Mutiani, Mutiani; Ilhami, M. Ridha (International Conference On Social Science Education, 2024)
Wordwall learning media can be utilized as one of the learning tools in the independent curriculum as it is currently implemented. Wordwall is a digital platform that enables teachers to create various types of interactive educational games, serving as a means of teaching and evaluation. This allows educators to explore alternative options and incorporate other subject matter in different formats. Fun and varied media will encourage students to become more active and motivated in the learning process. This study aims to determine whether the application of Wordwall learning media can improve students' critical thinking skills in junior high school especially at SMPN 8 Banjarmasin. This research uses a qualitative research method with an observational method. The results showed that Wordwall learning media can improve students' critical thinking skills through the use of interactive and fun educational games. By using Wordwall, students can develop critical and active skills in the learning process, such as searching, comparing, and evaluating information.